Siliceous sponges from the Upper Triassic-Lower Jurassic, Pucará Group, Peru: new evidence of a faunal recovery during the extinction event - Chacaltana Budiel, César Augusto (2016)
Across the Triassic-Jurassic transition, an important change in atmospheric pCO2 was recorded, concomitant with the eruption and emplacement of the Central Atlantic Magmatic Province and the splitting of Pangea. Upper Triassic carbonate producers were in full recovery after the Permian-Triassic Extinction. The Triassic-Jurassic marine crises produced an unexpected resurgence of siliceous sponges in detriment of carbonate skeletal fauna. This change of main sessile fauna, in shallow platforms communities, lasted for few millions years. Previous studies in Nevada (USA), Peru, Morocco, Austria and France show that this sponge event can be considered a global phenomenon. We report here the finding of Upper Triassic hexactinellid sponges in Pongo de Lorocache limestones, south edge of the Santiago basin, Peru. The sponges are found in the uppermost levels of the Chambará Formation. This unit exhibits sequences of the Upper Norian to Lower Rhaetian showing an unconformable contact with Jurassic sequences (Aramachay Formation). A great number of complete sponge body fossils occur in life position showing gregarious habits, they are associated with bivalves and ammonoids. This finding in the Norian- Rhaetian levels slightly predates the main peak of siliceous sponge dominance recorded in Lower Jurassic units, such as the overlying Aramachay Formation or the Sunrise Formation in Nevada.